The poetics of singularity : the counter-culturalist turn in Heidegger, Derrida, Blanchot and the later Gadamer /: the counter-culturalist turn in Heidegger, Derrida, Blanchot and the later Gadamer. ([2019?]) - Clark, Timothy, 1958-
No abstract available